Transient Heat Transfer and Energy Transport in Packed Bed Thermal Storage Systems - Li, Pei Wen; Lew, Jon Van; Karaki, Wafaa; Chan, Cho Lik; Stephens, Jake; O’Brien, James. E. (IntechOpen, 2011)
None